Grynfelt lumbar hernias. Presentation of a congenital case. - Cleopatra Cabrera Cuellar; Nilda B. Cortizo Martínez; Alina L. Díaz Dueñaz; Sergio Elías Molina Lamothe (Medisur)
Lumbar hernias are uncommon and are reported rarely, they are informed only few more than 300 in literature and of them only 10 cases are congenital. The hernias that are produced through the superior lumbar space or Grynfelt-Lesshalf´s hernia, are due to the fact that they are more constant and larger they are usually more frequent than the Petit triangle. We are reporting a Newborn infant with the diagnosis of bilateral lumbar hernias and malformation of the vertebral column.